Digital media foundations : an introduction for artists and designers / Richard Lewis and James Luciana - Lewis, Richard, 1955-; Luciana, James (Routledge, Taylor & Francis Group, 2020)
"Fully-updated and comprehensive, this second edition is a creative and practical introduction to the field of digital media for future designers, artists, and media professionals. It addresses the evolution of the field, its connections with traditional media, up-to-date developments, and possibilities for future directions. Logically organized and thoughtfully illustrated, it provides a welcoming guide to this emerging discipline. Describing each medium in detail, chapters trace their history, evolution and potential applications. The book also explains important, relevant technologies - such as digitizing tablets, cloud storage, and 3D printers - as well as new and emerging media like augmented and virtual reality. With a focus on concepts and creative possibilities, the text's software-neutral exercises provide hands-on experiences with each of the media. The book also examines legal, ethical, and technical issues in digital media, explores career possibilities, and features profiles of pioneers and digital media professionals. Digital Media Foundations is an ideal resource for students, new professionals, and instructors involved in fields of graphic and visual arts, design, and the history of art and design"- Resumé vydavatel